1971
DOI: 10.1136/bmj.1.5742.200
|View full text |Cite
|
Sign up to set email alerts
|

Injected Progestogen and Lactation

Abstract: SummaryNorethisterone ethanate (200 mg every 84 days) and medroxyprogesterone acetate (150 mg every three months) were found to be completely effective in fertility control when started in the puerperium. Neither agent had any ill effect on the amount of milk or the duration of lactation. From the third month onward the three-hourly available milk and the infant weight gain per month were statistically higher in treated groups than in controls. Milk proteins showed a slight decrease in most groups, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Boudraoui et al 32 found that immediate administration of DMPA postpartum in 772 lactating women followed from delivery to 1 year postpartum actually resulted in an increase in the amount of milk and an increase in protein concentration. Karim et al 33 found that administration of DMPA 7 days postpartum was not only associated with no adverse effects on the amount of milk production or duration of lactation, but the treatment group showed greater infant weight gain than did the control subjects. A 2002 study showed that breastfeeding women using progestin‐only methods of contraception that were initiated before hospital discharge had no significant differences in their continuation rates of breastfeeding when compared to breastfeeding women who used nonhormonal methods of contraception.…”
Section: Hormonal Methodsmentioning
confidence: 99%
“…Boudraoui et al 32 found that immediate administration of DMPA postpartum in 772 lactating women followed from delivery to 1 year postpartum actually resulted in an increase in the amount of milk and an increase in protein concentration. Karim et al 33 found that administration of DMPA 7 days postpartum was not only associated with no adverse effects on the amount of milk production or duration of lactation, but the treatment group showed greater infant weight gain than did the control subjects. A 2002 study showed that breastfeeding women using progestin‐only methods of contraception that were initiated before hospital discharge had no significant differences in their continuation rates of breastfeeding when compared to breastfeeding women who used nonhormonal methods of contraception.…”
Section: Hormonal Methodsmentioning
confidence: 99%
“…This drug causes hyperplasia of mammary secretory epithelium in macaques [ 114 ] and mice, with its activity being associated with epidermal growth factor (EGF) [ 115 ]. However, there are limited clinical studies in women suggesting that this drug is effective in increasing serum PRL and milk production [ 116 118 ]. Medroxyprogesterone acetate biological half-life in human is 40–60 hrs [ 119 ].…”
Section: Synthetic Galactogoguesmentioning
confidence: 99%
“…Indeed, studies have suggested an increase in breast milk volume with DMPA use. 49 A prospective observational study found that women using DMPA appeared to breastfeed for significantly longer than controls (21 months for DMPA users compared to 13 months for controls). 26 Use of DMPA also appeared to significantly increase the duration of exclusive breastfeeding (7 months for DMPA users compared to 5 months for controls).…”
Section: Progestogen-only Injectablementioning
confidence: 99%